Thermal ablation for pulmonary oligometastases from hepatocellular carcinoma: initial experience and retrospective study - Rongna Hou; Xueliang Zhou; Yipu Li; Yamin Qin; Mengyao Song; Chengzhi Zhang; Zhanguo Sun; Dechao Jiao (Cancer Imaging)
Abstract Objective To evaluate the long-term efficacy of thermal ablation in the treatment of pulmonary oligometastases (POs) from hepatocellular carcinoma (HCC) and to explore the prognosis-related influencing factors. Methods From October 2012 to January 2019, 145 POs (mean diameter: 2.3 cm, ≤ 4 POs per patient) in 62 patients (male = 33, female = 29, mean age: 61.0 years old) with HCC were treated by thermal ablation. The primary endpoints were progression-free survival (PFS) and overall survival (OS), and the secondary endpoints were technical success, technical efficacy, and complications. PFS and OS were analyzed by the log-rank test and Cox proportional hazards regression models. Results Technical success, technical efficacy and major complications were 100, 96.8, and 21%, respectively. During the median follow-up of 30 months (range: 16–50), the median PFS was 11.4 months (95% CI 10.1–12.8), the 1- and 2-year PFS rates were 43.5 and 10.2%, respectively, and radical treatments for primary HCC (P < 0.01), metachronous POs (P < 0.01) and initial Barcelona Clinic Liver Cancer (BCLC) stage 0-B (P < 0.05) were significant indicators of superior PFS. The mOS was 33.0 months (95% CI 26.9–39.1), and the 1-, 2- and 3-year OS rates were 98.4, 78.7% and 43.7%, respectively. Radical treatments for primary HCC (P < 0.01) and initial BCLC stage 0-B (P < 0.05) showed superior OS. Conclusion POs ablation after primary HCC control is safe and effective, and initial BCLC stage evaluation and radical treatment strategies should be emphasized. This study has certain limitations, including the retrospective design, single-center data, selection bias and small sample size.